THE EFFECT OF MIND MAPPING BASED ADVANCE ORGANIZER LEARNING MODEL ON STUDENTS' CREATIVE THINKING ABILITY - Liwis Muriharti; Maria Chandra Sutarja; Mochammad Ahied; Eva Ari Wahyuni; Wiwin Puspita Hadi (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2024)
This study aims to determine the effect of the mind mapping-based Advance Organizer learning model on students' creative thinking ability. The research method used is Quasi Experimental with the type of Nonequivalent Control Group the Design was carried out at one of Junior High School (JHS) in Ngimbang, Lamongan Regency, for the 2022/2023 Academic Year. Data collection techniques were carried out through tests. Hypothesis testing use independent sample t-test and analysis improving students' creative thinking ability using the N-Gain Score test. The results showed that: 1) There are differences between the creative thinking ability of class students in experimental and control classes with a significance value of 0.000 < 0.05 then H0 is rejected and H1 is accepted, 2) There is an increase in students ' creative thinking ability based on the N-Gain test the score in experimental class was 0.68 in medium category and control class it was 0.31 for medium category. We conclude that mind mapping-based Advance Organizer learning model has an influence on students' creative thinking ability.